Phase analysis‐based stationary clutter suppression under iron‐structures for automotive FMCW radar. Issue 5 (1st May 2019) - Lee, Jingu; Kim, Daehyun; Jeong, Seonghee; Kim, Younglok
Abstract : In this study, to reduce the performance degradation due to iron‐clutter, the authors propose a suppression method for stationary clutter under iron‐structures for an automotive radar using a frequency‐modulation continuous‐wave (FMCW) radar. The presence of a large number of iron‐structures such as iron‐bridges, soundproof walls, and iron‐tunnels creates a harsh environment that deteriorates the associated radar detection performance owing to clutter. To mitigate the adverse effects of clutter, they propose a clutter suppression scheme using up‐ and down‐chirp signals based on an analysis of signal characteristics. In particular, it is shown that the stationary clutters can be suppressed by making that the phases of the up‐chirp and down‐chirp are similar. To experimentally verify the proposed method, 77 GHz FMCW radar data for adaptive cruise control was acquired along a road on which several iron‐structures were located. The experimental results show that using the proposed clutter suppression scheme, the frequency of the moving target was detected well using the proposed clutter suppression scheme in an iron‐clutter‐rich environment. Through the application of the proposed clutter suppression scheme, stable target detection performance of the radar can be obtained.